The selective criminalization of vagrancy or non-work - Barros, Lúcio Mauro Paz (Seven Editora, 2023)
The conduct of idleness or non-work is typified as a criminal misdemeanor of vagrancy under the terms of Decree-Law no. 3.688 / 1941, article 59, providing for simple imprisonment from fifteen days to three months. In this sense, the present article discusses the historical and legal process of the criminalization of vagrancy (or non-work) through an empirical investigation, based on studies on Criminal System, Criminal Code and Criminal Offenses Act, in a legal interpretation sociological. It is hoped that the research will contribute to the deepening of the debate on the different political, legal and cultural aspects involved in the criminalization of vagrancy by collaborating cumulatively with legal science and social transformation from a human rights perspective. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-004